Peran Manajemen Sumber Daya Manusia dalam Menciptakan Keunggulan Bersaing Perusahaan - Dina Sarah Syahreza; Agung Khairul Tazri; Thasya Salsabila Berutu; Indah Febiola Fransiska Panggabean; Zefaninya Stephani Sinuraya (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
Human resource management supports companies to gain competitive advantage through business strategy. The aim of this research is to provide an overview of the role of human resource management (HRM) in establishing competitive advantage in companies and to find out which employee recruitment and training are best used to increase competitive advantage. The research method used is descriptive qualitative with literature review data collection techniques. Based on the results of the review, it is known that competitive advantage is achieved through the company's internal environment, namely human resources. Therefore, it is necessary to strengthen the company's internal environment through employee recruitment as well as employee training and development.